Causes of delay in preparation and settlement of final account / Alia Maisarah Aziz - Aziz, Alia Maisarah (2021)
Construction industries are a growing industry in Malaysia that encompasses housing, commercial and infrastructure development. The construction industry has a direct bearing on the national economy and can be used as an indicator of economic well-being for a country. Payment is always the issue in construction industry. Any delay in final account settlement can adversely affect the contractors' cash flow and the ability to secure its finance. Client related, contractor related and common to both client and contractor related issues are the categorized causes to the delay in settlement of final account. However, it depends on the type of contract used as well as the time allocation in the preparation of final account. Those factors are need to be considered other than dispute between both parties which contributes the most to the delay alongside with other factors such as delay in submitting claim or client withhold the payment. Hence, the aim of this research is to identify the problems associated with the delay in settlement of final account. Data collection for this paper includes survey using questionnaires which were distributed among the Quantity Surveyors. The outcome of this research will includes problems related to delay in final account, causes of delay in preparation and settlement of the final account and the suggestions to minimize delay in final account.